ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI (2009-2011) (Students' Journal of Accounting and Banking, 2013)
The aim of this research is to examine the influence of size company, profitability, financial leverage and auditor reputation toward to income smoothing practice among manufacture companies listed at Indonesia Stock Exchange . Income smoothing is a tool that is used by management to reduce fluctuations in earnings reporting and accounting to manipulate variables. In this study, Eckel index is used to determine income smoothing practices.The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange, in periode between 2009-2011. The total of 145 companies, which meet the criteria for purposive sampling method was 79 manufacturing companies.This research analyzed using descriptive statistics and tested by logistic regression (binary logistic regression). The results of logistic regression showed that firm size, profitability, financial leverage and auditor reputation did not significantly affect the practice of income smoothing.Keywords: income smoothing, size companies, profitability, financial leverage and auditor reputation